Low self-control and imprudent behavior - Arneklev, Bruce J. (Journal of quantitative criminology, 1993)
Gottfredson and Hirschi's A General Theory of Crime contends that individual differences in involvement in criminal and analogous behavior are due largely to individual differences in the personality trait they call low self-control. Among the various behaviors considered analogous to crime are imprudent behaviors such as smoking, drinking, and gambling. This research explores the generality of Gottfredson and Hirschi's theory by examining the link between low self-control and these imprudent behaviors. The results are mixed. In support of the theory, the data reveal a modest but significant effect of a scale designed to capture the various components of low self-control on an index of imprudent behavior. A more detailed analysis, however, reveals that some of the components of low self-control, specifically those probably linked to low intelligence, detract from the scale's predictive power. In fact, one of the components, risk-seeking, is more predictive than the more inclusive scale. Furthermore, one of the imprudent acts, smoking, appears to be unaffected by low self-control. These contradictory findings suggest the need for theoretical refinements.